A scoping review of outcome measures for people living with dementia and family supporters to evaluate Recovery College dementia courses - Alam, Jarin; West, Juniper; Moniz-Cook, Esme; Wolverson, Emma; Handley, Melanie; Birt, Linda; Fox, Chris (Frontiers in Psychiatry, 2025)
IntroductionRecovery Colleges (RC/RCs) aim to promote personal recovery through co-produced courses, grounded in the CHIME (Connectedness, Hope, Identity, Meaning, Empowerment) framework. The DiSCOVERY research programme noted that RC dementia courses may offer a person-centred approach to post-diagnostic dementia care. However, the lack of validated outcome measures for this context presents a challenge in evaluating RCs’ effectiveness. This scoping review examines the potential outcome measures for evaluating the impact of RC dementia courses.MethodsThe review followed the Arksey and O’Malley framework, searching for eligible papers across six databases related to dementia and the CHIME strengths-based approach. Instruments relating to personal recovery and positive psychology for people with dementia or their family supporters were included. Measures of cognition, clinical symptoms, or ‘negative constructs’ (e.g., burden) were excluded. DiSCOVERY stakeholder groups (people with dementia and clinicians) met to collaboratively identify meaningful domains and relevant measures.ResultsFourteen instruments relating to hope, resilience, self-efficacy, empowerment, and coping were identified. Stakeholders of people living with dementia endorsed domains of empowerment, resilience, and hope. No single instrument captured the range of outcomes that underlie the concepts of the RC dementia course.DiscussionThis study contributes to the limited literature on instruments for the evaluation of concepts underlying RC dementia courses. Findings suggest a need for adaptation and further validation of existing measures, to address responsiveness, interpretability, and the inclusion of domains related to recovery. Future research on recovery in the context of dementia should involve developing or adapting new measures, conducting feasibility studies, and exploring cultural sensitivity for diverse populations.